A qualitative investigation of physical activity compensation among older adults. Issue 1 (24th November 2017) - Gray, Phillip; Murphy, Marie; Gallagher, Alison; Simpson, Ellen Elizabeth Anne
Abstract : Objectives: This study explored the mechanisms of physical activity (PA) compensation among older adults who recently reduced their non‐exercise physical activity (NEPA) in response to a structured PA intervention. Design: A post‐trial, retrospective qualitative process evaluation using interviews was employed. Methods: Levels of PA compensation were determined by comparing NEPA prior to and during the final week of a 4‐week structured PA intervention. Those who reduced their NEPA by 10% or greater were considered as compensators. Interviews were conducted with older adult compensators (mean age = 58.56 ± 3.88 years; n  = 9), employing thematic analysis to identify potential mechanisms of PA compensation. Results: The findings suggest that the majority of participants were unaware that they had compensated in their PA, suggesting that this may be a non‐volitional process. Most participants perceived PA compensation to hold negative implications for health and well‐being. Physiological processes of fatigue and delayed onset of muscle soreness were cited as the principal cause of PA compensation, whereas psychological processes including a drive to be inactive, fear of overexertion, deficient motivation, and perceived time constraints were cited to a lesser extent. Conclusion: A range of physiological and psychological compensatory barriers were identified. Implications of and methods to overcome these compensatory barriers are discussed. Statement of contribution What is already known on this subject? Physical activity compensation holds negative implications for physical activity promotion and health. Older adults are an age group more likely to compensate in their physical activity levels. What does this study add? Physical activity compensation may be a result of a range of physiological and psychological processes including fatigue and delayed onset of muscle soreness, compensatory health beliefs, fear of overexertion, deficient motivation, and perceived time constraints. Most older adult compensators may be unaware they are compensating and, however, agree that physical activity compensation has negative implications for health and well‐being.